Evaluación in vitro de la eficacia antibacteriana de los irrigantes endodonticos hipoclorito de sodio al 1% a temperatura de 37º y agua ozonizada frente a una cepa de enterococcus faecalis (atcc 29212) - Carhuayo Matta, Miguel Augusto (2011)
The objective of this study was to determine the antibacterial efficacy of sodium hypochlorite 1% at a temperature of 37 ° C and ozonized water 20 mg / L against a strain of Enterococcus faecalis in vitro. 20 petri dishes were evaluated with the strain of enterococcus faecalis sown. 10 with sodium hypochlorite solution and 10 with the ozonated water was observed the formation of CFU at 24 and 48 hours. In relation to the ozonated water 20 mg / L the average colony forming units (cfu) of Enterococcus faecalis was found was equal to 3.49 x 106 cfu in 24 days and 48 hours, no differences were statistically significant (p <0.05) between both times. In relation to NaOCL 1% at a temperature of 37 ° C the average colony forming units (cfu) of Enterococcus faecalis in 24 days and 48 hours was 0. When comparing the 1% NaOCl at a temperature of 37 ° C and the ozonated water 20 mg / L was found statistically significant differences in the times 24 and 48 hours (p = 0,001).